2021
DOI: 10.3390/ijerph18042000
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Online Voluntary Self-Exclusion in Gambling: An Empirical Study Using Account-Based Behavioral Tracking Data

Abstract: Online gambling has continued to grow alongside new ways to analyze data using behavioral tracking as a way to enhance consumer protection. A number of studies have analyzed consumers that have used voluntary self-exclusion (VSE) as a proxy measure for problem gambling. However, some scholars have argued that this is a poor proxy for problem gambling. Therefore, the present study examined this issue by analyzing customers (from the gambling operator Unibet) that have engaged in VSE. The participants comprised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 43 publications
(70 reference statements)
0
12
1
Order By: Relevance
“…Griffiths and Auer (2016) highlighted that there are limitations in this latter approach because gamblers may not be using self-exclusion for problem gambling reasons. A recent study by Catania and Griffiths (2021) analysed 7732 gamblers who had used VSE. They reported almost one-fifth of the gamblers used the VSE option even though the players had less than 24 h of activity on their account.…”
Section: Discussionmentioning
confidence: 99%
“…Griffiths and Auer (2016) highlighted that there are limitations in this latter approach because gamblers may not be using self-exclusion for problem gambling reasons. A recent study by Catania and Griffiths (2021) analysed 7732 gamblers who had used VSE. They reported almost one-fifth of the gamblers used the VSE option even though the players had less than 24 h of activity on their account.…”
Section: Discussionmentioning
confidence: 99%
“…Their analysis also found that self-excluders made riskier bets than the control group. Catania and Griffiths (2021b) compared players who closed their account due to a specific self-reported gambling addiction with players who chose a six-month account closure option. Players who chose to close their account for six months had low gambling activity and had only registered recently (i.e., just over 50% of gamblers self-excluded within seven days of opening a gambling account, with one-fifth self-excluding within 24 h of opening an account).…”
Section: Problem Gambling Indicators Using Data From Gamblers Who Hav...mentioning
confidence: 99%
“…Finally, the authors did not have access to players' self-reported reasons for self-exclusion. Previous research has shown that self-excluders are a heterogenous population (Catania & Griffiths, 2021b).…”
Section: Limitationsmentioning
confidence: 99%
“…However, this assumption is controversial. Several studies have shown that problem gamblers may not self-exclude, while non-problem gamblers may self-exclude for reasons other than problem gambling (Griffiths & Auer 2016b;Catania & Griffiths, 2021b;Price-waterhouseCoopers & Responsible Gaming Council of Canada, 2017). On the other hand, there is also literature that has reported relationships between behavior patterns and selfreported/diagnosed problem gambling using survey and interview data (Bagby et al, 2007;McCormack et al, 2013;Sproston et al, 2000).…”
Section: Introductionmentioning
confidence: 99%